Speech and harm controversies over free speech - Maitra, Ishani; McGowan, Mary Kathryn, 1968- (Oxford : Oxford University Press, 2012)
Most liberal societies are committed to free speech, but there is evidence that some kinds of speech can be harmful in ways that are detrimental to important liberal values, such as social inequality. This volume draws on a range of approaches to explore the problem and determine what should be done about allegedly harmful speech.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Freedom of speech -- Social aspects